Introduction to adiabatic shear localization - Dodd, Bradley; Bai, Yilong (Imperial College Press, 2015)
Adiabatic shear bands are found in a variety of metals and other materials; they cause rapid weakening due to energy concentration into narrow regions of the material. This is the very first book on this important topic and the only true introduction to the subject.